Mapping and assessing ecosystem service supply–demand to identify critical areas: A case study of a waterside area in Shanghai metropolitan area - Ni, Yuchun; Wei, Jiaxing; Wu, Tao; Guo, Min; Han, Qiyao; Zhang, Mingjuan (Frontiers in Earth Science, 2022)
In the past decades, rapid urbanization in China has dramatically transformed natural spaces into construction land, leading to serious degradation and supply-demand imbalance of ecosystem services (ESs). The identification of critical areas and ecological security pattern is crucial for balancing ESs and improving human well-being in rapidly urbanized regions. The purpose of this study is to establish a comprehensive assessment framework of ESs supply-demand including provisioning, regulating, supporting and cultural services, so as to provide theoretical support for the identification and refined management of regional critical areas. Taking a typical waterside area in Shanghai Metropolitan Area as an example, based on multi-source data and ESs quantitative models, we used ecological supply-demand ratio and bivariate local indicators of spatial association to quantify the relationship and matching patterns of ESs supply-demand, then explored the identification, protection and restoration of ecological critical areas at the regional scale. The results showed that: (1) The ESs supply-demand relationship in the study area was quantitatively determined. The ESDR was as follows: regulating > provisioning > supporting > cultural, in which the supply of supporting and cultural services was less than the demand, and the problem of supply-demand mismatch is prominent; (2) We have identified 41 supply critical areas that require priority protection, with a total area of 206.79 km2 accounting for 9.65% of the total study area, showing a spatial pattern of more in the northwest and less in the southeast; (3) Eleven demand critical areas that need ecological restoration were identified, accounting for 31.43% of the 35 administrative towns in the study area, which are mainly distributed around three urban centres and a high-tech zone. The study is of great significance for the construction of regional ecological security pattern and rational ESs allocation, and can provide a scientific framework for the ecological protection and restoration of critical areas around metropolises in developing countries.